Down to Earth, Up for Democracy - Wu, Yuxuan (Hungarian Journal of English and American Studies, 2022)
Book review: Gregory, Elizabeth. Apparition of Splendor: Marianne Moore Performing Democracy through Celebrity, 1952–1970. Newark: U of Delaware P, 2021. 264 pages. ISBN 9781644531969. Hb. 34.95.